Variability in geochemical weathering indices in loess over the last full glacial cycle at Karamaidan, central Asia (Tajikistan) - Aquino, Andrea; Scardia, Giancarlo [UNESP]; Prud’homme, Charlotte; Dave, Aditi K.; Lezzerini, Marco; Johansson, Alexandra Engström; Marquer, Laurent; Safaraliev, Nosir; Lauer, Tobias; Fitzsimmons, Kathryn E. (Frontiers, 2024)
This study presents the first quantitative assessment of weathering conditions in the Tajikistan depression throughout the last full glacial cycle. We employed geochemical and magnetic susceptibility analyses to investigate various weathering indices (WIs), with the CPA and FENG indices identified as the most suitable for this region. Our results confirm the formation of a robust pedocomplex, PS2, during the OIS5 interglacial phase, while primary loess deposition occurred during the interstadials. The presence of a weak paleosol, PS1, suggests that OIS3 was not significantly pronounced, and sediment transport and deposition continued during this period. Furthermore, we assessed the effectiveness of various climatic transfer functions, including some recently developed specifically for Chinese loess. These transfer functions have also shown promising applicability to the loess of Central Asia, producing realistic climate trends that are, however, still to be taken with caution. The MAT and mean annual precipitation generated with these functions show for the last interglacial period about 13°C and 665 mm, thus higher temperatures and lower precipitation than the current conditions of 10.8°C and 730 mm. These results indicate a significant increase (c. 15%) in both temperature and precipitation compared to the stadial periods.
Keywords: central Asia; Karamaidan; loess-palaeosol sequences; Tajikistan; weathering index